206k views
2 votes
Solve using substitution: y=4-2x and 3x+2y=7

User Kospiotr
by
4.9k points

2 Answers

6 votes

Answer:

The solution is (1, 2)

Explanation:

The expression 4 - 2x is equivalent to y. Thus, we can eliminate y by substituting 4 - 2x for y in 3x + 2y = 7:

3x + 2(4 - 2x) = 7, or

3x + 8 - 4x = 7

Combining like terms, we get:

-x = - 1, or x = 1. If x = 1, then (from y = 4 - 2x) y = 4 - 2(1) = 2

The solution is (1, 2)

User Matt Spoon
by
4.9k points
4 votes

Answer:

(1,2 )

Explanation:

use m a t h w a y, it gives you the right answers every time

User Behrooz Tabesh
by
5.4k points